2006
DOI: 10.2215/cjn.00630206
|View full text |Cite
|
Sign up to set email alerts
|

N-3 Fatty Acids as Secondary Prevention against Cardiovascular Events in Patients Who Undergo Chronic Hemodialysis

Abstract: Patients who are treated with chronic hemodialysis (HD) experience premature cardiovascular disease and an increased mortality. N-3 polyunsaturated fatty acids (PUFA) may be effective in the secondary prevention of cardiovascular disease, but the effects of n-3 PUFA has not previously been examined in HD patients. It was hypothesized that secondary prevention with n-3 PUFA would reduce the number of cardiovascular events and death in patients who are treated with chronic HD. A randomized, double-blind, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 38 publications
2
99
0
Order By: Relevance
“…Whether these effects are applicable to RTRs is unclear. In patients who are uremic and treated with hemodialysis, high intake of marine n-3 PUFAs was associated with a lower risk of SCD (17), and an RCT found a lower cumulative incidence of MI after marine n-3 PUFA supplementation (16). In RTRs, there have been reports of improved renal function with marine n-3 PUFA supplementation (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these effects are applicable to RTRs is unclear. In patients who are uremic and treated with hemodialysis, high intake of marine n-3 PUFAs was associated with a lower risk of SCD (17), and an RCT found a lower cumulative incidence of MI after marine n-3 PUFA supplementation (16). In RTRs, there have been reports of improved renal function with marine n-3 PUFA supplementation (29).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ESRD, favorable effects of marine n-3 PUFAs on cardiovascular morbidity and mortality have been shown (16,17). Although renal transplantation reduces the risk of CVD in patients with ESRD, CVD remains the leading cause of death in recipients of renal transplants (RTRs) (18).…”
Section: Introductionmentioning
confidence: 99%
“…Kutner et al [5] reported that mortality in patients on HD decreased with fish consumption; however, mortality from cardiac and cardiovascular diseases was similar between patients on HD who consumed fish (60%) and those who did not (61%). Svensson et al [19] conducted a clinical trial with n–3 PUFAs for secondary prevention of CHD in patients on HD and observed no significant effect on the primary composite endpoint of total cardiovascular events and death. However, as a secondary outcome, they found that the incidence of myocardial infarction was significantly reduced in the group treated with n–3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional studies of omega-3 PUFAs have investigated the potential effectiveness of PUFA treatment in reducing CV risk in patients on hemodialysis. These include studies of treatment with fish oil dietary supplements containing EPA, DHA, and other ingredients as well as studies of purified products that contain both EPA and DHA or only EPA; results were varied [24,25,26,27,28,29]. Here, we examine the interventional outcomes studies of EPA-only therapy in hemodialysis patients as well as the effects of EPA on factors such as lipids, inflammation, and oxidative stress, which are likely to play a role in the increased CVD risk in this patient population.…”
Section: Eicosapentaenoic Acid As a Potential Therapeutic Approach Tomentioning
confidence: 99%